Tourism in Bali and the challenge of sustainable development - Pickel Chevalier, Sylvine (Cambridge Scholars Publishing, 2017)
This work offers a cross-analysis of the development of tourism in Bali, combining international and intercultural (from Indonesian, French, Australian and English researchers), transdisciplinary and inter-generational research. It questions the capacity of tourism, to be a vector of sustainable development, by analyzing its various social, economic and environmental effects within Balinese society. As such, it represents not only a great research tool, but a fantastic teaching aid. Each chapter comes with its own bibliography, and thus acts as a standalone case study, while making a contribut.